The “Becoming” in Teaching: A Reflection on Doing and the Construction of Being Through the Teacher–Student Relationship - Aranda Aguirre, Ximena; Fermandois Poblete, Paulina (Relatos Journal, 2025)
This essay reflects on the concept of “becoming” in university teaching in Occupational Therapy, understanding teaching as an occupation with deep symbolic and transformative meaning. Based on Ann Wilcock’s propositions regarding being, doing, and becoming, it analyzes how teaching and student identities are constructed dialectically, in relation to the sociopolitical context and shared experiences. Teaching is addressed not only as an academic act, but as a human encounter that leaves traces and enables processes of personal and collective transformation. The text proposes understanding “becoming” as a dynamic process linked to occupational identity, fulfillment, and life projection, in which relationships and the environment play a determining role. From this perspective, it is suggested that teachers and students co-construct scenarios of possibility in higher education, where diversity, inclusion, and mutual recognition are fundamental pillars. Likewise, the importance of educational environments that facilitate, sustain, and encourage this process is highlighted, enhancing well-being and autonomy. Finally, the essay invites a rethinking of teaching as a situated practice that harmonizes past, present, and future, in which individual and collective trajectories intertwine, enabling a shared and meaningful “becoming”.